Mental Health Status Among UNIMAS Medical Students During the Pandemic Covid-19 - Ramli, Norhida; Zhimin, Foong; Mohammed, Maziah Fathiah; Rasid, Aizuddin Zhafri; Othman, Nurodarina; Ahmad Razali, Shazrina (Universitas Muhammadiyah Semarang, 2023)
Background: Due to the outbreak of Covid-19, medical students were suffering from poor mental health, leading to depression, anxiety, and stress. Research to better understand mental health is essential because of the high prevalence of poor mental health among students during the pandemic.Objective: Therefore, the study aims to determine the mental health status of UNIMAS medical students during the Covid-19 pandemic. In this study, the predictive validity of the Depression, Anxiety, and Stress Scale (DASS-21) for the presence of a depressive disorder and its associated coping factors were investigated among medical students.Methods: A cross-sectional study was conducted among medical students from the University Malaysia Sarawak's Faculty of Medicine and Health Sciences. The DASS-21 was administered to 411 respondents, and data were analyzed using Man-Whitney and Chi-Square tests.Results: The result showed that most medical students had normal levels of depression (75.7%), anxiety (74.2%), and stress (92.5%). The highest coping method used was rest and sleep (95.1%), followed by singing and listening to music (91.5%).Conclusion: Most UNIMAS medical students were in good mental health during the COVID-19 pandemic. They tend to have a better-coping mechanism before the stressful condition deteriorates.